The Acquisition of Word Classes in the Indonesian Language by Students with Hearing Impairments - Septiani, Dwi; Zainal Rafli; Fathiaty Murtadho; Tryana (Universitas Negeri Semarang, 2024)
This study explores the acquisition of word classes among deaf students in special education over one academic year (2023/2024), focusing on developing their language skills. Through the analysis of 668 words categorized according to Harimurti Kridalaksana's theory, the research reveals that nouns dominate (37.4%), followed by verbs (22.4%), adjectives (14.9%), adverbs (11.9%), pronouns (7.5%), conjunctions (4.5%), and prepositions (1.2%). These findings suggest that hard-of-hearing children or deaf students focus on concrete objects and actions, indicating a reliance on tangible language in communication. The lower use of pronouns, conjunctions, and prepositions points to more superficial sentence structures, highlighting the need for explicit naming and connections in their writing. The study underscores the need for educators to adapt their teaching strategies to support language acquisition for deaf students better. It recommends bilingual interventions integrating sign and spoken language, emphasizing visual and contextually relevant instruction. The study also calls for targeted support in teaching verbs and adjectives. It advocates for creating interactive, experiential learning environments that foster emotional support and engagement, which can enhance language mastery and communication skills. Additionally, the research highlights the importance of professional development for educators to address the unique linguistic and cognitive challenges faced by deaf students. Finally, it encourages longitudinal research to investigate linguistic dimensions in their language acquisition further. This study aims to contribute to more effective educational practices that promote optimal language development and social integration for deaf children